Evaluation of Anti-Diarrhoeal Activity of Different Bark Extracts of Faidherbia albida (Delile) A (Chav) in Albino Rats - Timothy, S.Y; Wazis, C.H; Midala, T.A.S; Joseph, O.S; Sabastine ,A.Z; Nachanaa, T; Oiza, F.D (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2017)
Diarrhoea is a major concern in the health sector as it is the second leading cause of death and growth retardation in children under five years old, and is responsible for killing significant number of children every year. Various drug treatments available are not readily accessible, affordable and may have associated adverse or side effects, and in some cases resistance to antimicrobial agents have developed. This research focuses on the antidiarrhoeal activity of the aqueous and ethanol extracts of Faidherbia albida bark commonly used in herbal medicine in the Northern part of Nigeria to treat diarrhoeal diseases. The phytochemical screening of the bark extracts of Faidherbia albida revealed the presence of alkaloids, carbohydrates, flavonoids, saponins and tannins. However, glycoside was not found in both extracts. Both extracts had significant antidiarrhoeal effect. The ethanol extract was found to have higher antidiarrhoeal activity when compared to the aqueous extract. The extracts of Faidherbia albida bark had dose dependent activity in castor oil induced diarrhoea by significantly reducing the number of wet faecal droppings and delayed time of onset of diarrhoea. The bark extracts of Faidherbia albida was found to contain phytochemicals which may be responsible for the antidiarrhoeal activity and this justifies the traditional use of this plant in the treatment of gastrointestinal diseases including diarrhoea.